Importance of application development for Korean rice cake culture succession and adolescent obesity - Han, Ji Ahn; Kwon, Ki Han (Progress in Nutrition, 2023)
Background and aim: Globally, it has been reported that obesity among adolescents increases the rate of overweight and obesity due to genetic factors, unbalanced diet, and a high-fat, high-sugar diet. Obesity in adolescence is increasing in severity as it can lead to adult obesity and even chronic diseases. Based on this awareness of problems, the modern society is attracting the attention to the excellence of Korean traditional food, rice cakes, while pursuing health-oriented thinking. In addition, as the influence of the Korean Wave and interest in Korean food are growing, foreigners visiting Korea are also increasing. However, there is a lack of professional applications that contain information about rice cake, a traditional Korean food. Therefore, this study aims to establish proper eating habits during adolescence, which is greatly affected by growth and development, and to inspire the importance of the history of Korean traditional food, rice cake. Methods: It is necessary to develop mobile applications that can promote rice cake, so we would like to introduce the importance of rice cake culture and nutrition education in Korea, healthy rice cake recipes to prevent various diseases, as well as information about rice cake shops overseas and in Korea. Results: It appeared that they were looking for knowledge and information on obesity management and nutrition. It was found that Korean rice cakes should be inherited and developed for its valuable cultural resource to future generations. Accordingly, it was found that it would be useful when developing applications for the succession of rice cake culture and adolescent obesity. Conclusions: This is expected to promote rice cake, a traditional Korean food, and increase the frequency of rice cake consumption.